Empirical Evidence on the Link Between Compliance with Governance of Best Practice and Firms' Operating Results - Tek B Lama (Australasian Accounting, Business and Finance Journal, 2013)
This study provides robust evidence in support of the agency theory argument that corporate governance matters for a firm’s operating performance. Using the corporate governance ratings as the governance proxy from Horwath 2006 Corporate Governance Report (mid-sized Australian ASX companies) and Mid-Cap Corporate Governance Report 2007 (The University of Newcastle 2006; 2007), I examine 60 sample firms to reveal that a firm’s governance is positively and significantly related to firm performance as measured by return on equity, earning yield and return on assets. This study extends the findings of these two reports which found a disturbing trend in the corporate governance practice of Australian mid-cap companies – both a decrease in companies with excellent corporate governance, and an increase in companies with significant corporate governance deficiencies. The findings of this study suggest that those mid-size companies who have allowed corporate governance to deteriorate have adversely affected their shareholder returns.
Keywords: Corporate governance; Agency theory; Mid-cap; Best practice; Horwath report